Delivery of adipose-derived growth factors from heparinized adipose acellular matrix accelerates wound healing - Ru, Jiangjiang; Zhang, Qian; Zhu, Shaowei; Cai, Junrong; He, Yunfan; Lu, Feng (Frontiers in Bioengineering and Biotechnology, 2023)
Dermal white adipocytes are closely associated with skin homeostasis and wound healing. However, it has not been fully investigated whether adipose-derived products improve wound healing. Here, we obtained adipose acellular matrix (AAM) and adipose-derived growth factors (ADGFs) from human adipose tissue and fabricated an ADGF-loaded AAM via surface modification with heparin. The product, HEP-ADGF-AAM, contained an adiposederived scaffold and released ADGFs in a controlled fashion. To test its efficacy in promoting wound healing, mice with full thickness wound received three different treatments: HEP-ADGF-AAM, AAM and ADM. Control mice received no further treatments. Among these treatments, HEP-ADGF-AAM best improved wound healing. It induced adipogenesis in situ after in vivo implantation and provided an adipogenic microenvironment for wounds by releasing ADGFs. HEP-ADGF-AAM not only induced adipocyte regeneration, but also enhanced fibroblast migration, promoted vessel formation, accelerated wound closure, and enhanced wound epithelialization. Moreover, there was a close interaction between HEP-ADGF-AAM and the wound bed, and collagen was turned over in HEP-ADGF-AAM. These results show that HEP-ADGF-AAM might substantially improve re-epithelialization, angiogenesis, and skin appendage regeneration, and is thus a promising therapeutic biomaterial for skin wound healing.